Modification and performance evaluation of KAU low cost paddy thresher - ANU VARGHESE NANCY K. VARGHESE; Er. George Mathew (Guide) (Tavanur 1993 Kelappaji College of Agricultural Engineering and Technology)
paddy cultivation. KAU product. paddy thresher
Modification and performance evaluation of KAU low cost paddy thresher